INTERACTIVE AND GAME-BASED ENGLISH LEARNING FOR ELEMENTARY STUDENTS THROUGH COLLABORATIVE TEACHING: A CASE QUALITATIVE STUDY - Gabriel Fredi Daar; Fithriyah Inda Nur Abida; Fahri Fahri (Program Studi PGSD Universitas Flores, 2025)
Despite the growing recognition of interactive and game-based learning in language education, limited research has explored how collaborative teaching strategies can effectively enhance elementary students’ motivation, confidence, and language learning in rural Indonesian contexts. This study aims to investigate the effectiveness of interactive and game-based English learning through collaborative teaching strategies in enhancing elementary students’ motivation, confidence, and language acquisition. The study was conducted at SDK Ri’I, Cibal Distric, Manggarai, East Nusa Tenggara, Indonesia. Using a case qualitative study approach, data were collected through classroom observations, student interviews, and teacher reflections. The participants of the study were one teacher and 25 students who involved in the teaching and learning process. The participants were taken purposively based on predetermine criteria. The findings revealed that the integration of games and interactive activities through collaborative teaching strategy increased student engagement, fostered a supportive learning environment, and improved vocabulary comprehension and pronunciation. Students showed enthusiasm, active participation, and a strong sense of collaboration during group-based tasks. However, challenges such as varying proficiency levels, fluctuating attention spans, and the need for diverse game types were also identified. Despite these challenges, the approach proved successful in promoting both cognitive and affective development. The study highlighted well-designed interactive strategies to make learning enjoyable and support holistic language development. Thus, it’s essential to integrate interactive and game-based methods through collaborative teaching strategy in English language instruction at the elementary level.